(untitled) (Contemporary Journal of Social Science Review, 2025)
One of the largest investment and infrastructure initiatives in South Asia is the China-Pakistan Economic Corridor (CPEC). The degree to which locals are compensated is crucial to the availability of human capital, even if it is anticipated to bring about economic evolution and create a lot of jobs. This research study assesses the actual gaps and human capital limitations that impact Balochistan’s capacity to take advantage of the CPEC employment opportunities. There is a significant discrepancy between the skills needed in the CPEC-linked businesses and the capabilities of the local workforce, as demonstrated by primary survey data, labor market statistics, and qualitative interviews from important economic zones in Balochistan.The analysis’s conclusions demonstrate that, despite higher infrastructure investment, Balochistan’s employment outcomes are hampered by low educational attainment, inadequate vocational training, gender disparities, and institutional barriers. The study suggests targeted human capital policies to support infrastructure investments and promote inclusive growth.